Cicaprost, an orally active prostacyclin analogue: its effects on platelet aggregation and skin blood flow in normal volunteers. - Belch, J J (1993)
1. Prostacyclin (PGI2) and its analogues may be useful in peripheral vascular disease. However, most have to be given intravenously due to their metabolic instability. 2. We have investigated the pharmacological effects of cicaprost, a synthetic PGI2 analogue which is metabolically stable and bioavailable after oral administration, in eight healthy male volunteers. 3. This was a double-blind, placebo-controlled, cross-over study. The volunteers were given either placebo, 5 micrograms, 7.5 micrograms or 10 micrograms cicaprost (at 09.00 h, 14.00 h, 19.00 h and again at 09.00 h the following day) on four separate occasions each 14 days apart. 4. Platelet aggregation induced by collagen and ADP in platelet rich plasma (PRP) and whole blood were measured prior to and 1 h after the trial medication. Laser Doppler flowmetry measured skin blood flow on the face before and after medication. 5. There was a statistically significant dose relationship in the inhibition of platelet aggregation induced by 2 microM ADP and 0.4 microgram ml-1 collagen in PRP and 2 microM ADP and 0.6 microgram ml-1 collagen in whole blood by cicaprost (P = 0.008, P = 0.34, P = 0.011 and P = 0.036, respectively). The threshold dose was 7.5 micrograms. Attenuation of anti-platelet effects was seen with the 14.00 h and 19.00 h doses. This may be due to a decrease in absorption after meals or to the development of tachyphylaxis. 6. Similar dose dependent effects of cicaprost on skin blood flow were also found (P = 0.01 and P = 0.006 for maximum output signal and red blood cell flux, respectively). The threshold dose was 7.5 micrograms. 7. In conclusion, cicaprost has significant anti-platelet and vasodilatory effects when given in doses of 7.5 micrograms and 10 micrograms three times a day in healthy male volunteers.